Urban restorative landscape: a cultural inquiry of redesigning Chester I. Lewis Reflection Square Park - Sun, Wei (Kansas State University, 2018)
Living in a healthy environment is one of the basic desires of modern society, but is particularly hard to achieve in urban settings where the access to green urban space is limited. Restorative landscapes, healing gardens, and therapeutic gardens can improve mental and physical health. Environmental psychology has a long tradition of research from which landscape architects can learn the benefits of natural environments (Ulrich 1984). Exposure to a natural environment is known to result in increased physiological well-being, improved mood, pleasure (Ulrich 1984). More recently, cross-disciplinary research on spending time in nature has shown that it can provide benefits for human health, both physically and psychologically (Krinke 2005). Examples of restorative settings can be found throughout history and are still applied today in health-care facilities as healing or restorative gardens. A healing garden’s wide significance in the urban public realm and outcome for community engagement remains insufficiently exposed. Many urban environments lack the beneficial restorative properties of nature for healing and recovering. This report will focus on understanding and exploring how a restorative landscape can be implemented within an urban area to create a multi-functional place with potential to relieve different kinds of stress and improve overall well-being. The site for this investigation is Chester I. Lewis Reflection Square Park (Lewis Park) in downtown Wichita, Kansas. Lewis Park focuses on a famous part of Wichita’s civil rights history: Chester I. Lewis and his role in the Dockum Drugstore Sit-in of 1958. The park currently consists of an interactive fountain and series of sculptures. I will develop the design proposal through various methods, such as archival research, site inventory and analysis, precedent study research, stakeholder engagement and interviews. A team of three students addressed this project in partnership with Downtown Wichita. My specific project focuses on understanding the park condition, why Lewis park is failing, and how to improve the park to meet users’ demands. The site needs to be redesigned for local people seeking a restorative environment for their daily lives.
Keywords: Urban restorative landscape